2011
DOI: 10.1016/j.immuni.2011.04.020
|View full text |Cite
|
Sign up to set email alerts
|

The Costimulatory Molecule CD27 Maintains Clonally Diverse CD8+ T Cell Responses of Low Antigen Affinity to Protect against Viral Variants

Abstract: CD70 and CD27 are costimulatory molecules that provide essential signals for the expansion and differentiation of CD8(+) T cells. Here, we show that CD27-driven costimulation lowered the threshold of T cell receptor activation on CD8(+) T cells and enabled responses against low-affinity antigens. Using influenza infection to study in vivo consequences, we found that CD27-driven costimulation promoted a CD8(+) T cell response of overall low affinity. These qualitative effects of CD27 on T cell responses were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
143
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 41 publications
(57 reference statements)
5
143
1
1
Order By: Relevance
“…This failure to recapitulate the magnitude of the T-cell response to Poly I:C/αCD40 indicates that IL-27 cannot completely replicate the complex inflammatory environment instigated by the TLR agonist. We and others previously published on an important role for CD70-CD27 interactions in the T-cell response to combined TLR/ CD40 immunization (24,25,54) as well as to infectious challenge/ vaccination (55)(56)(57)(58). Because IL-27 and CD27 separately are required for maximal T-cell responses after subunit vaccination, neither alone is therefore sufficient for maximal T-cell expansion.…”
Section: Discussionmentioning
confidence: 99%
“…This failure to recapitulate the magnitude of the T-cell response to Poly I:C/αCD40 indicates that IL-27 cannot completely replicate the complex inflammatory environment instigated by the TLR agonist. We and others previously published on an important role for CD70-CD27 interactions in the T-cell response to combined TLR/ CD40 immunization (24,25,54) as well as to infectious challenge/ vaccination (55)(56)(57)(58). Because IL-27 and CD27 separately are required for maximal T-cell responses after subunit vaccination, neither alone is therefore sufficient for maximal T-cell expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The crucial role of CD70-driven costimulation becomes evident postinfection with acute viruses such as vaccinia virus, vesicular stomatitis virus, and the A/NT/60/68 strain of the influenza virus, during which CD70 and CD27 essentially contribute to the size of the CD8 T cell response (14,21). Recently, we found that CD27 does not have an apparent role in the regulation of the size of primary CD8 T cell responses postinfection with other strains of influenza (22). Close inspection revealed that CD27 favors the outgrowth of low-affinity CD8 T cells at the cost of high-affinity CD8 T cells, suggesting that the costimulatory effects of CD27 depend on the affinity of the Ag interactions (22).…”
mentioning
confidence: 94%
“…Recently, we found that CD27 does not have an apparent role in the regulation of the size of primary CD8 T cell responses postinfection with other strains of influenza (22). Close inspection revealed that CD27 favors the outgrowth of low-affinity CD8 T cells at the cost of high-affinity CD8 T cells, suggesting that the costimulatory effects of CD27 depend on the affinity of the Ag interactions (22). In fact, CD27 enhances the cell death of CD8 T cells stimulated with high-affinity Ags, whereas CD27 improves T cell survival after stimulation with similar amounts of low-affinity Ags (22).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, whether CD27 similarly plays a role during memory T-cell activation has been less clear; many studies that sought to address this question have made use of CD27-deficient or CD70-overexpressing mice in which interpretation of the memory CD8 + T-cell response is complicated by the impact of CD27/CD70 signals on CD8 + T-cell priming/imprinting and memory differentiation [6,9,12,41,42]. Furthermore, the remaining studies have reported conflicting results.…”
Section: Discussionmentioning
confidence: 99%